HUBUNGAN PENGETAHUAN ORANGTUA SISWA TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT DENGAN KEJADIAN KARIES PADA ANAK KELAS V SDN SUKAKARYA - Nina Marlina Marlina; Denden Ridwan Chaerudin; Neneng Nurjanah; Tri Widyastuti (Jurnal Terapi Gigi dan Mulut, 2021)
Introductin : Maintenance of oral health is one of the efforts to improve health. One reason someone ignores the problems of oral health is the lack of knowledge about dental and oral hygiene. The role of parents is very important in assisting children in maintaining oral health, the role of parents is as caregivers, educators, supporters and supervisors. Dental caries is a disease of dental caries tissue caused by certain microorganisms that have the ability to form acids, especially in the presence of carbohydrates, which will result in a low salivary pH which can cause the dissolution of enamel minerals slowly. Objective : The aim of this study was to determine the relationship of parents' knowledge about dental and oral health care with caries incidence in fifth grade students of SDN Sukakarya 101 Bandung. Method : This type of research is analytical research using cross sectional design. The population in this study were all students of class V SDN Sukakarya 101 Bandung, amounting to 29 people and 29 mothers. Sampling in total sampling of students and parents of class V SDN Sukakarya 101, Arcamanik District of Bandung, which amounted to 29 students and 29 parents. The research instrument used in the form of a questionnaire level of maternal knowledge and observation sheet of dental caries incidence of children. Result : Based on the test decision, it was concluded that there was a significant relationship between parents' knowledge about dental and oral health maintenance with caries incidence in class V students of SDN Sukakarya 101 Bandung with an x2 obs value of 13,241 with p-value = 0,000. Because the observation p-value is smaller than 0.05 (0,000 <0.05). Conclusion : Terdapat hubungan tingkat pengetahuan orang tua dengan kejadian karies pada anak